Academic charisma and the origins of the research university - Clark, William, 1953- (University of Chicago Press, 2006)
Tracing the transformation of early modern academics into modern researchers from the Renaissance to Romanticism, Academic Charisma and the Origins of the Research University uses the history of the university and reframes the "Protestant Ethic" to reconsider the conditions of knowledge production in the modern world. William Clark argues that the research university--which originated in German Protestant lands and spread globally in the nineteenth and twentieth centuries--developed in response to market forces and bureaucracy, producing a new kind of academic whose goal was to establish originality and achieve fame through publication. With an astonishing wealth of research, Academic Charisma and the Origins of the Research University investigates the origins and evolving fixtures of academic life: the lecture catalogue, the library catalog, the grading system, the conduct of oral and written exams, the roles of conversation and the writing of research papers in seminars, the writing and oral defense of the doctoral dissertation, the ethos of "lecturing with applause" and "publish or perish," and the role of reviews and rumor. This is a grand, ambitious book that should be required reading for every academic